2018
DOI: 10.5222/sscd.2016.96268
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trail Using A Silver-Coated Screw-Rod System and One-Year Follow-Up of The First 50 Patients

Abstract: The occurrence of implant-related infection in all surgical branches is one of the challenges for which a definitive solution has yet to be found. One way to reduce the incidence of implant-related infection is to use implants which are coated with antibacterial materials such as silver. The aim of this study is to investigate if the nanoparticle silver coated spinal implants reduce the implant related infection rates and safe for human use. Method: In this clinical trial performed with 50 patients, we investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Ag-related adverse reactions, such as argyria and mental or neurological disorders [ 31 ], hepatic and renal dysfunction [ 32 ], cytotoxicity [ 33 ], and mutagenicity [ 34 ], can result from a total dose of 4 g of Ag or a blood Ag concentration of ≥ 300 ppb [ 23 , 32 ]. Regarding neurological damage, Seçinti et al reported that the implantation of 23 g of Ag does not cause neuropathy, based on the listed dental literature [ 35 ]. The maximum amount of Ag contained in the Ag-HA implant for THA and the double cage was reported to be 3 mg [ 15 ] and 1.6 mg, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Ag-related adverse reactions, such as argyria and mental or neurological disorders [ 31 ], hepatic and renal dysfunction [ 32 ], cytotoxicity [ 33 ], and mutagenicity [ 34 ], can result from a total dose of 4 g of Ag or a blood Ag concentration of ≥ 300 ppb [ 23 , 32 ]. Regarding neurological damage, Seçinti et al reported that the implantation of 23 g of Ag does not cause neuropathy, based on the listed dental literature [ 35 ]. The maximum amount of Ag contained in the Ag-HA implant for THA and the double cage was reported to be 3 mg [ 15 ] and 1.6 mg, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…33 In addition, the authors of a 2017 clinical trial in Turkey using a titanium-silver nanoparticle-dipped screw-rod system reported no infections in 50 patients, and undetectable serum/urine silver levels over a 1-year study period. 34 Historically, the MUTARS (Modular Universal Tumor And Revision System; implantcast, Buxtehude, Germany) and other silver ion-coated titanium alloy endoprostheses have been used in Europe for tumor orthopedic reconstruction due to their inherently high risk of postoperative SSIs (up to 47%). 3 The MUTARS system was first introduced in 1992.…”
Section: Silvermentioning
confidence: 99%
“…Trovarelli [ First, most reports of orthopedic antimicrobial implants have been for surgical operations using antimicrobial implants for extremity fractures [119,156] or antimicrobial megaprosthesis for bone tumor reconstruction surgery in the extremities, which is associated with a relatively high infection rate [6,31,[136][137][138][139][140][141][142][143][144][145][146][147][148][149], with spinal application described in few cases [117,[151][152][153][154]. Moreover, as for the type or site of the spinal antimicrobial instrumentation, the pedicle screw is expected based on the frequency of use and the intervertebral cage from the viewpoint of host-site immunity; however, most cases of clinical use described the use of antimicrobial pedicle screws.…”
Section: Antimicrobial Implants For Clinical Use In Orthopaedic and S...mentioning
confidence: 99%